Islam, orientalism and intellectual history : modernity and the politics of exclusion since Ibn Khaldun - Salama, Mohammad R. (I. B. Tauris & Co Ltd, 2011)
As the events and aftermath of 9/11 have shown, the relationship between Islam and the West is deeply troubled. Here Mohammad Salama calls for a new understanding of Islam as a historical condition that has existed in relationship to the West since the seventh century. He compares the Arab-Islamic and European traditions of historical thought since the early modern period, focusing on the watershed moments that informed their ideas of intellectual history and perceptions of one another. Islam, he argues, has played a major role in enabling and positioning Western historiography at key points, leaving palpable imprints on Islamic historiography in the process. Focusing on Ibn Khaldun, the complexities of orientalism and modernity, and recent European as well as Arab writings on these themes, this book is essential for all those interested in Islamic and Middle Eastern studies, Western and Islamic philosophies of history, and modernity. -- Publisher's description